Globalization and Digitalization in the Dynamics of Economic Welfare in ASEAN and BRICS Countries - Bestari, Mohamad Fidelio Omar (IBLAM LAW REVIEW, 2025)
This study examines the dynamics of economic welfare in ASEAN and BRICS countries within the context of globalization and digitalization, as measured by per capita income, unemployment rates, and poverty levels. Employing a panel data regression method covering 15 countries over the period 2007–2024, the findings indicate that globalization and digitalization shape welfare patterns that are heterogeneous and highly dependent on country-specific characteristics. Globalization, represented by trade openness and foreign direct investment (FDI), is associated with increases in per capita income and reductions in unemployment, although its impact on poverty alleviation remains uneven. Meanwhile, digitalization, measured through internet penetration, demonstrates a significant positive association with income growth and poverty reduction, underscoring the role of digital technology in expanding economic inclusion. Beyond global factors, welfare dynamics are also influenced by domestic conditions, particularly the quality of governance and the effectiveness of social policies. These findings highlight the importance of integrated and adaptive development strategies that respond to global dynamics and digital transformation. Policy recommendations include strengthening institutional capacity, promoting joboriented investment, and expanding digital infrastructure and literacy to narrow socioeconomic disparities in the era of digital globalization.